A novel SRC-2-dependent regulation of epithelial-mesenchymal transition in breast cancer cells. Issue 185 (January 2019) - Bozickovic, Olivera; Skartveit, Linn; Engelsen, Agnete S.T.; Helland, Thomas; Jonsdottir, Kristin; Flågeng, Marianne Hauglid; Fenne, Ingvild S.; Janssen, Emiel; Lorens, James B.; Bjørkhaug, Lise; Sagen, Jørn V.; Mellgren, Gunnar
Graphical abstract: Highlights: SRC-2 depletion induces mesenchymal-to-epithelial transition. SRC-2 expression negatively correlates with luminal and cell morphogenesis genes. SRC-2 regulates the expression of the EMT biomarker Lyn. Abstract: Steroid receptor coactivator 2 (SRC-2) is a nuclear receptor coactivator, important for the regulation of estrogen receptor alpha (ERα)-mediated transcriptional activity in breast cancer cells. However, the transcriptional role of SRC-2 in breast cancer is still ambiguous. Here we aimed to unravel a more precise transcriptional role of SRC-2 and uncover unique target genes in MCF-7 breast cancer cells, as opposed to the known oncogene SRC-3. Gene expression analyses of cells depleted of either SRC-2 or SRC-3 showed that they transcriptionally regulate mostly separate gene sets. However, individual unique gene sets were implicated in some of the same major gene ontology biological processes, such as cellular structure and development. This finding was supported by three-dimensional cell cultures, demonstrating that depletion of SRC-2 and SRC-3 changed the morphology of the cells into epithelial-like hollow acinar structures, indicating that both SRC proteins are involved in maintaining the hybrid E/M phenotype. In clinical ER-positive, HER2-negative breast cancer samples the expression of SRC-2 was negatively correlated with the expression of MCF-7-related luminal, cell cycle and cellular morphogenesis genes. Finally, elucidating SRC-2 unique transcriptional effects, we identified Lyn kinase (an EMT biomarker) to be upregulated exclusively after SRC-2 depletion. In conclusion, we show that both SRC-2 and SRC-3 are essential for the EMT in breast cancer cells, controlling different transcriptional niches.